Building Character and Digital Literacy through Comics - Hawa, Andina Meutia; Pratiwi, Anne; Pratiwi, Dyani Prades; Nesa, Fakhria; Saniro, Roma Kyo Kae; Arbain, Armini (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
Comics can be categorized as literary works because they contain stories, ideas, and thoughts. Comics have at least two elements, such as images, and narration, which are interrelated. The pictures in comics are intended to stimulate interest in reading, develop imagination, and provide aesthetic elements. Therefore, comics can be used as a communication medium to convey stories and moral messages to readers and build character and digital literacy. This research aims to explain the role of comics as a medium for building character and digital literacy in the stories contained in the collection of children's comics published by Mizan and the Komik Next G series published by Muffin Graphics. Comic stories are written by writers for children aged 8-13 years and illustrated by professional comic artists. This research uses analytical descriptive methods. This research uses two kinds of data, namely primary and secondary sources. The data collection technique used in this research is the library technique. Based on the results of the analysis, it was found that the four stories used as research objects contained character education values, namely honesty and reminding each other in kindness, as well as being competitive and competing in a healthy manner; and the value of digital literacy, namely being wise in using devices, as well as using technology to develop talents, and the importance of supervision in using technology. The value of honesty and reminding each other in kindness are found in the story entitled Jujur itu Penting; the value being competitive in healthy manner is found in the story Kunci Juara Kelas. The value of digital literacy in the form of being wise and responsible in using devices is found in the story Gara-Gara Wi-Fi; The value of digital literacy in using technology for future development and the importance of supervision in using technology is found in the story of Mangaka Cilik.